Training Effects of the FIFA 11+ Kids on Physical Performance in Youth Football Players: A Randomized Control Trial - Pomares-Noguera, Carlos; Ayala, Francisco; Robles-Palazón, Francisco Javier; Alomoto-Burneo, Juan F.; López-Valenciano, Alejandro; Elvira, José L. L.; Hernández-Sánchez, Sergio; De Ste Croix, Mark (Frontiers in Pediatrics, 2018)
Objective: To analyse the training effects of the FIFA 11+ Kids on several parameters of physical performance in male youth football players. Material and Methods: Twenty-three youth players were randomised within each team into two groups (control vs. intervention). The intervention group performed the FIFA 11+ Kids programme 2 times a week for 4 weeks; the control groups completed their normal warm-up routines. Thirteen physical performance measures (range of motion [hip, knee and ankle joints], dynamic postural control [measured throughout the Y-balance test], 20 m sprint time, slalom dribble with a ball, agility, vertical jumping height [counter movement jump and drop jump], horizontal jump distance, accuracy when volleying a ball [measured throughout the Wall Volley test]) were assessed. All physical performance parameters were compared via magnitude-based inference analysis. Results: Significant between-group differences in favour of the FIFA 11+ players were found for dynamic postural control (anterior [mean and 90% confidence intervals [CI] = 1 cm, from -1.6 to 3.5 cm] and posteromedial [mean and 90% CI = 5.1 cm, from -1.8 to 12 cm] and posterolateral [mean and 90% CI = 4.8 cm, from 0.6 to 9.0 cm] distances), agility run (mean and 90% CI = 0.5 s, from -0,9 to 0 s), vertical jump height (counter movement jump [mean and 90% CI = 3.1 cm, from 0.2 to 6.1 cm] and drop jump [mean and 90% CI = 1.7 cm, from -0.5 to 3.9 cm]), and horizontal jump distance (mean and 90% CI = 2.5 cm, from -8 to 15 cm). The control groups showed better performance in 20 m sprint time (mean and 90% CI = -0.05 s, from -0.11 to 0.07) and wall volley tests (mean and 90% CI = 0.2, from -0.2 to 0.6) compared to the intervention group. Conclusions: The main findings of this study suggest that just 4 weeks of implementation of the FIFA 11+ Kids produces improved physical performance compared with traditional warm up routines in youth soccer players.